Preparación de rendición de cuentas de tesorería para auditoria del año 2012 (2013)
The Departmental Comptrollership Quindío as a public accounting entity that develops public functions of state assignment that controls public resources has the obligation of render account on the use of these resources and the maintenance of public property in order to demonstrate to the users of the information legality and transparency in the effected processes.